2013
DOI: 10.1016/j.neubiorev.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Recovering from cocaine: Insights from clinical and preclinical investigations

Abstract: Cocaine remains one of the most addictive substances of abuse and one of the most difficult to treat. Although increasingly sophisticated experimental and technologic advancements in the last several decades have yielded a large body of clinical and preclinical knowledge on the direct effects of cocaine on the brain, we still have a relatively incomplete understanding of the neurobiological processes that occur when drug use is discontinued. The goal of this manuscript is to review both clinical and preclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 96 publications
2
32
0
1
Order By: Relevance
“…Gaining a better idea of neurofunctional changes during treatment represents an important first step in understanding the neurobiology of successful abstinence (Garavan et al, 2013;Hanlon et al, 2013). Additionally, our findings of increased precuneus/PCC activity during A2Win are consistent with a recent meta-analysis citing common effects of pharmacological and cognitive-based interventions in these areas (Konova et al, 2013).…”
Section: Strengths Limitations and Future Directionssupporting
confidence: 88%
See 1 more Smart Citation
“…Gaining a better idea of neurofunctional changes during treatment represents an important first step in understanding the neurobiology of successful abstinence (Garavan et al, 2013;Hanlon et al, 2013). Additionally, our findings of increased precuneus/PCC activity during A2Win are consistent with a recent meta-analysis citing common effects of pharmacological and cognitive-based interventions in these areas (Konova et al, 2013).…”
Section: Strengths Limitations and Future Directionssupporting
confidence: 88%
“…Although many neuroimaging studies examine chronic effects of cocaine on cognitive processes, relatively few examine brain changes occurring with discontinued drug use (Garavan et al, 2013;Hanlon et al, 2013). Investigating neurofunctional changes associated with abstinence may provide important insights regarding strategies for cessation and relapse prevention (Garavan et al, 2013;Hanlon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with control subjects, cocaine users have lower resting-state functional connectivity within the mesolimbic DA system and lower network connectivity between limbic regions is correlated with duration of cocaine use (Gu et al, 2010). Indeed, a recent review article concluded that loss of PFC function during abstinence could be the most reliable clinical biomarker of relapse (Hanlon et al, 2013;Bough et al, 2014).…”
Section: Cortical Dysregulation and 5-ht 2a/c Receptor Functionmentioning
confidence: 99%
“…This leads to a prolonged cycle of abuse, treatment, and relapse (e.g., Griffin et al, 1989;Vonmoos et al, 2013). Neurologic decrements from long-term cocaine intake may persist a year beyond cessation of use (review by Hanlon et al, 2013). These can include impaired attention, working memory, and executive function (Vonmoos et al, 2013(Vonmoos et al, , 2014, possibly owing to decreased frontal lobe activity (Volkow et al, 1992;Connolly et al, 2012).…”
Section: Introductionmentioning
confidence: 99%